(untitled) (Proceeding Of Sari Mulia University Midwifery National Seminars, 2023)
Background: Every pregnant woman experiences anatomical and physiological changes in her body. One of the discomforts that occurs during the third trimester of pregnancy from 28 weeks to 40 weeks of pregnancy is lower back pain, where a pregnant woman complains of pain around the back to the waist. This is due to changes in the center of gravity in the body as compensation due to increasing body weight Objective: To determine the effectiveness of pregnancy exercise and pregnancy yoga on reducing back pain in third trimester pregnant women at PMB WM Banjarmasin. Methods: This study uses a quasi-experimental type with pretest and posttest group design techniques. In this study, the sample was divided into 2 groups, namely the pregnancy exercise group and the pregnancy yoga group. Based on the results of sample calculations using case control, there were 10 respondents who took part in pregnancy exercise and 10 respondents who took part in pregnant yoga in January 2023 at PMB WM Banjarmasin. Sampling using porpusive sampling technique. Collecting data using observation and analyzed using the t test. Results: Pregnancy exercise is effective in reducing back pain in third trimester pregnant women at PMB WM Banjarmasin. Pregnant yoga is effective in reducing back pain in third trimester pregnant women at PMB WM Banjarmasin. Conclusion: Pregnancy exercise and pregnancy yoga are effective in reducing back pain iaaan third trimester pregnant women at PMB WM Banjarmasin.